2014
DOI: 10.1097/mpg.0000000000000457
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of Emergency Department Use in Pediatric Inflammatory Bowel Disease

Abstract: Objectives We sought to characterize emergency department (ED) encounters for pediatric inflammatory bowel disease (IBD) to identify areas for prevention. Methods Retrospective chart review of 5 consecutive ED encounters at 7 centers was performed. Results Of 35 unique encounters by 32 patients, 3 main factors contributed to ED utilization: disease severity or course, day or time of care, and physician instruction. Of the ED encounters, approximately one-fifth were judged medically unnecessary, and one-hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Our results also support the findings of Hoffenberg et al, 6 who showed that there was an opportunity to reduce ED visits in a subset of pediatric gastroenterology patients with inflammatory bowel disease. Otherwise, there is little in the literature examining ED use among pediatric specialists.…”
Section: Discussionsupporting
confidence: 82%
“…Our results also support the findings of Hoffenberg et al, 6 who showed that there was an opportunity to reduce ED visits in a subset of pediatric gastroenterology patients with inflammatory bowel disease. Otherwise, there is little in the literature examining ED use among pediatric specialists.…”
Section: Discussionsupporting
confidence: 82%
“…IBD-related emergency department (ED) visits are an important area of concern since it is over-utilized by the IBD patients and is a potential target for cost savings [7]. In a recent pediatric IBD study, it was found that at least one-half of all ED encounters could have been avoided in a more responsive and coordinated healthcare system [8]. While the epidemiology of the hospitalized adult IBD patients has been comparatively well studied, the data from the ED setting remain limited [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It might not be true emergencies and probably could be managed on an outpatient basis because the ER visits did not often result in a hospitalization or surgery. Hoffenberg et al[10] found that one-fifth ER visits for IBD were judged medically unnecessary, and one-half avoidable in a more optimal health care system. van Deen et al [23].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to reduce the utilization of acute care services in relation to the quality of care for chronic intestinal BD and intestinal BD-related disease management. In a recent pediatric IBD study, it was found that at least one-half of all ER visitors could have been avoided in the presence of a more responsive and coordinated health-care system [10]. …”
Section: Introductionmentioning
confidence: 99%